Stormwater as an Alternative Source of Water Supply: Feasibility and Implications for Watershed Management - Sanjay Shukla; Fouad H. Jaber (EDIS)
Circular 1493, a 6-page circular by Sanjay Shukla and Fouad H. Jaber illustrated with maps and graphs, discusses the feasibility of using water from an alternative source of water supply for southern Florida that is usually not considered -- water held in urban/agricultural storm water detention/retention (impoundment) areas. The authors describe the results of a feasibility study of an impoundment in a citrus grove in the southern part of the Caloosahatchee River Basin. Includes references. Published by the UF Department of Agricultural and Biological Engineering, July 2006.